Response of Root Growth and Development to Nitrogen and Potassium Deficiency as well as microRNA-Mediated Mechanism in Peanut (Arachis hypogaea L.) - Li, Lijie; Li, Qian; Davis, Kyle E.; Patterson, Caitlin; Oo, Sando; Liu, Wanying; Liu, Jia; Wang, Guo; Fontana, Julia Elise; Thornburg, Thomas Elliott; Pratt, Isaac Seth; Li, Fei; et al. (Frontiers in Plant Science, 2021)
The mechanism of miRNA-mediated root growth and development in response to nutrient deficiency in peanut (Arachis hypogaea L.) is still unclear. In present study, we found that both N and K deficiency resulted in significant reduction in plant growth, as indicated by the significantly decreased dry weight of shoot and root under N or K deficiency. Both N and K deficiency significantly reduced the total root length, root surface area, root volume, root vitality, and weakened root respiration, as indicated by the reduced O2 consuming rate. N deficiency significantly decreased primary root length and lateral root number, which might be associated with the up-regulation of miR160, miR167, miR393, and miR396, and the down-regulation of AFB3 and GRF. While the responses of primary root and lateral root to K deficiency were opposite to that under N deficiency condition. The up-regulated miR156, miR390, NAC4, ARF2, and AFB3, and the down-regulated miR160, miR164, miR393, and SPL10 maybe contributed to the growth of primary root and lateral root under K deficiency. Overall, roots responded differently N or K deficiency stresses in peanut, which potentially due to the miRNAs-mediated pathway and mechanism.